Legal Implications On Credit Agreements For Couple And Wife In Marriage Agreements After Marriage - Adessya Thalia Chairunissa; Liza Priandhini (Faculty of Law, Universitas Pekalongan, 2022)
A marriage that is legally carried out by husband and wife will have legal consequences for both parties that have an impact on the legal relationship between the two, including property in marriage. In this case, the Civil Code and the Marriage Law recognize the concept of